The lonely nerd - Schaper, B (University of Warwick, 2022)
This is the twenty-second issue of Exchanges, published in August 2022. This is our fourth special issue focussing on cultural experiences around the theme of the lonely nerd. Developed in collaboration with scholars from the Universities of Oxford and SOAS, and with author contributions from around the world, the issue is in part an output from a workshop held at the University of Warwick in spring 2021. Article topics in this issue include: conceptions and perceptions of lonely nerds, diversity of nerd representation in film, television theatre, gaming and comic books, along with explorations of alienation, non-conformity and societal acceptance. Within the issue’s editorial the Editor-in-Chief briefly introduces the issue and its development, alongside providing an overview of its articles and the future opportunities for contributions from authors old and new alike. An introductory essay from the two special issue leads provides an overview of the workshop and special issue themes, providing a useful framing for readers in contextualising the articles within.